A performance comparison of MD5 authenticated routing traffic with EIGRP, RIPv2 & OSPF - Mohd Tahir, Hatim; Abu Al-Saud, Khalid; Saleh, Moutaz; Saleh, Mohammed (Zarqa Private University, 2009)
Routing is the process of forwarding data across an inter-network from a designated source to a final destination. Along the way from source to destination, at least one intermediate node is considered. Due to the major role that routing protocols play in computer network infrastructures, special cares have been given to routing protocols with built-in security constraints. In this paper, we conduct performance evaluation comparisons on MD5 authenticated routing traffic with respect to EIGRP, RIPv2 and OSPF protocols. A network model of four Cisco routers has been employed with an ON/OFF traffic model used to describe text files transmissions over the network. Eventually, analysis tool has been developed and used to measure the average delay time and average jitter. The collected results show that the average delay time and jitter in the secured MD5 case can become significantly larger when compared to the non-secured case even in steady state conditions. Among all, the secured OSPF protocol shows the highest performance even when the system is extremely overloaded.